PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (Studi Pada Perusahaan Non-Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Dewi Puspita Sari, 10.05.52.0188; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2014)
The purpose of this research is to examines the effect of tax planning and deferred tax expense on earnings management. Identification of companies that used in the practice of earnings management is done by applying earnings distribution approach. Earnings distribution approach identified earnings thresholds and found that companies are in the below of earnings thresholds will attempt to pass the limit by earnings management. The population in this study are all companies listed on the Indonesia Stock Exchange (IDX) in the year 2011 to the year 2013. Total sample study for three years of observation is 201 samples. Sample used in this study is a non-manufacturing company which is added by entering the financial industry, sampling in this study was done by using purposive sampling. Purposive sampling of the population is intentionally based assessment or specific criteria. The results showed that tax planning have positive significant affect on earnings management and based on the results obtained that the deffered tax expense is have negative no significant affect on earnings management.Keywords: earnings management, tax planning, and deferred tax expense